2014
DOI: 10.3109/10428194.2014.951844
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic studies in children with acute lymphoblastic leukemia in Argentina

Abstract: The aim of this study was to evaluate the influence of the most common genetic variants in methylenetetrahydrofolate reductase (MTHFR), thiopurine methyltransferase (TPMT) and glutathione-S-transferases (GSTs) on the outcome of acute lymphoblastic leukemia (ALL) treatment in Argentinean children. Two hundred and eighty-six patients with ALL treated with two Berlin-Frankfurt-Münster (BFM)-based protocols were analyzed. Ten genetic variants were studied. Toxicity was evaluated during the consolidation phase. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…The spectrum and frequency of heterozygotes (10·5%) is similar to that observed for other Latin‐American and European populations. However, the ITPA 94A variant frequency (5·3%) was higher than that reported for a Chilean population (Silva et al , ; Farfan et al , ; Aráoz et al , ). Interestingly, 11 of the 115 individuals analysed were heterozygous for NUDT15 variants: five for NUDT15*2 , two for *3 , one for *4 and three for *6 .…”
Section: Association Between Risk Alleles Of Tpmt and Nudt15 And The mentioning
confidence: 57%
“…The spectrum and frequency of heterozygotes (10·5%) is similar to that observed for other Latin‐American and European populations. However, the ITPA 94A variant frequency (5·3%) was higher than that reported for a Chilean population (Silva et al , ; Farfan et al , ; Aráoz et al , ). Interestingly, 11 of the 115 individuals analysed were heterozygous for NUDT15 variants: five for NUDT15*2 , two for *3 , one for *4 and three for *6 .…”
Section: Association Between Risk Alleles Of Tpmt and Nudt15 And The mentioning
confidence: 57%
“…Neutropenia was analyzed in 4 studies. Only the study of Aráoz et al26 found risk 677T allele associated to neutropenia in patients who received low doses of MTX (2 g/m 2 ). None of the other 3 studies found association.…”
Section: C677t Polymorphism Analysismentioning
confidence: 99%
“…From them, only 5 found significant associations with toxicity, but with contradictory results: 2 studies related the T variant allele to a decrease in toxicity risk,24,25 whereas the other 3 associated it to increased risk (Table 1). 2628…”
Section: C677t Polymorphism Analysismentioning
confidence: 99%
See 2 more Smart Citations